2013
DOI: 10.1590/1414-431x20133013
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and anesthetic activities of the essential oils of Hyptis mutabilis (Rich.) Briq. and their isolated components in silver catfish (Rhamdia quelen)

Abstract: This study evaluated the sedative and anesthetic effects of the essential oils (EO) of Hyptis mutabilis (Rich.) Briq. and their isolated components on silver catfish (Rhamdia quelen). Quantitative chemical differences between the EOs obtained from leaves and inflorescences were verified, and a new chemotype rich in globulol was described. Although there were no significant differences in the time of induction for sedation and anesthesia between the EOs, only the leaf EO at 344 mg/L anesthetized all fish withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Ethanol controls were also tested at the same concentrations used for the dilutions corresponding to the highest EO concentrations. To evaluate the time required for anesthesia induction, 10 juveniles were used for each concentration and EO tested, and each juvenile was used only once, according to Silva et al (2013a). All fish were fasted the day prior to sampling.…”
Section: Experiments 1: Anesthetic Induction and Recoverymentioning
confidence: 99%
“…Ethanol controls were also tested at the same concentrations used for the dilutions corresponding to the highest EO concentrations. To evaluate the time required for anesthesia induction, 10 juveniles were used for each concentration and EO tested, and each juvenile was used only once, according to Silva et al (2013a). All fish were fasted the day prior to sampling.…”
Section: Experiments 1: Anesthetic Induction and Recoverymentioning
confidence: 99%
“…In aquaculture, anesthetics (synthetics or plant extratives) are widely employed: from light sedation, to reduce stress during handling and non-invasive procedures, to full anesthesia to avoid pain during surgery and larger interventions (Small, 2003;Roubach et al, 2005;Ross, Ross, 2008;Kiessling et al, 2009;Neiffer, Stamper, 2009;Silva et al, 2013a;Roohi, Imanpoor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The anesthetic efficacy of several essential oils (EOs), such as Hyptis mutabilis (Silva et al, 2013a), Ocotea acutifolia (Silva et al, 2013b), Hesperozygis ringens (Silva et al, 2013b;Toni et al, 2014), Aloysia triphylla and Ocimum gratissimum , has been demonstrated in fish. The EO of Lippia alba has been highlighted in the last decade through studies reporting its potential as antioxidant, anesthetic and sedative for fish (Cunha et al, 2010;Becker et al, 2012;Heldwein et al, 2014;Toni et al, 2014;Hohlenwerger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As regards the EOO, one of its main constituents is terpinen-4-ol, which has presented sedative effect at low concentrations (3-10 mg L -1 ) in R. quelen (Silva et al, 2013a). Another major compound of EOO, cis-terpineol, has anesthetic activity and modulating GABA A capacity (Watt et al, 2008), but so far no anesthetic activity was related to the other compounds found in EOC and EOO.…”
Section: Discussionmentioning
confidence: 99%